Simulating the Effect of Temperature Change on the Properties of a Quantum Dot Solar Cell - Khalel Zahoo, Raid; N. Abdullah, Q. (Tikrit Journal of Pure Science, 2026)
To develop solar cell technology, it is essential to focus on improving its efficiency at the temperatures typically encountered during operation. This study used third-generation quantum-dot solar cells (ITO/NiO/GaAs/CdTe/ZnO/Al). These cells exhibit electrical and optical properties suitable for photovoltaic applications. The impact of temperature on the performance of quantum dot solar cells is simulated using Silvaco Atlas, a tool for simulating experimental solar cells. The temperature in this work ranged from (300 K) to (350 K). The results confirmed a decrease in the solar cell's overall photovoltaic performance with increasing temperature. The electricity conversion performance decreased from (11 %) to (9.36 %), and the fill component reduced from (81.06 %) to (78.14 %). The open-circuit voltage also decreased from 0.98 V to 0.87 V. The short-circuit current density decreases slightly from (13.839 mA/cm2) to (13.7642 mA/cm2) with increasing temperature. The maximum energy of the solar cell also decreased from (2.2×10-11W) to (1.87×10-11 W) with growing temperature. This study revealed that the optimal temperature for the solar cell is 300 K, i.e., room temperature.